ANALYSIS OF INVENTORY PLANNING FOR COOKING OIL IN THE TANK OF PT INDOFOOD CBP SUKSES MAKMUR TBK NOODLE DIVISION SEMARANG BRANCH - Jesica Kartika Aritonang; Agung Budiatmo (International Journal of Economic Integration and Regional Competitiveness, 2024)
In inventory management, supervision is a crucial part of optimizing the efficiency and effectiveness of the cooking oil storage warehouse's operations. Inventory planning is key to ensuring optimal cooking oil storage, avoiding shortages due to spills or leaks, and reducing company losses. This study aims to evaluate cooking oil inventory planning considering inventory methods, control, and warehouse supervision. This research employs a qualitative research method with a descriptive approach. Data sources include primary data obtained through interviews, observations, secondary data from company documents, and supporting books related to inventory planning. Data collection techniques include field observations, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. The research findings indicate that cooking oil inventory planning in the tank warehouse using the PDCA method (Plan, Do, Check, Act) can enhance inventory management efficiency and effectiveness. Supporting factors include the transformation of manual supervision systems into automation to enable more efficient monitoring. However, supervision constraints persist due to the lack of automation systems for real-time monitoring and limitations in warehouse operational staff, resulting in less effective operations. The use of planning methods with PDCA can improve cooking oil inventory management in the warehouse, enhancing operational efficiency, and reducing inventory risks or excesses.